Technological innovation driving sustainable entrepreneurial growth in developing nations - Asabere, Nana Yaw; Gyimah, Glenn Kwabena; Acakpovi, Amevi; Plockey, Florence (Advances in Logistics, Operations, and Management Science (ALOMS), 2023)
Developing nations in Africa need access to advanced technology, innovation, and entrepreneurial skills for sustainable development as they address challenges that face the world at large in the 21st century. Since Ghana's development indices (high or low) remain deeply rooted in the measure of education provided to its citizens, the nation must seriously and continuously invest in university education and technological and entrepreneurial skills to enhance sustainable development. The strategy for sustainable development in Ghana appears to be well planned for global and regional agendas, with higher education serving as a panacea. Education 2030 Framework for Action (EFA) and the African Union Agenda 2063 provide foundations for the transition to the Sustainable Development Goals (SDGs) with the promise of technological and entrepreneurial innovation, as well as education for all.Technological Innovation Driving Sustainable Entrepreneurial Growth in Developing Nations builds a bridge of communication between the worlds of education and business through the exploration of critical research on the fight against poverty, hunger, malnutrition, and disease. This book also examines the interplay between entrepreneurial education and sustainable economic development in developing countries. Covering topics such as engineering technologies, entrepreneurship, and communication technologies, this book is ideal for researchers, educators, business administrators, students, and more.